Rozkład Strat w Kołowej Palisadzie Sprężarki Osiowej - Kral, J. (Engineering Transactions, 1973)
Based on published results of experimental investigations, a qualitative picture of the total pressure losses in viscous flow through axial rows of blades is presented, with particular consideration of the three-dimensional flow phenomena and their effects on boundary-layer growth and the associated secondary flows, resulting in vortex formation. Reviewed are the methods of calculation which have now been proposed for individual and compound losses and for radial distribution of the losses in blade rows of axial fans and compressors.